Fenomena akun pseudonim sebagai sarana pengungkapan diri (self-disclosure) pada Generasi Z pengguna akun media sosial x (Twitter) - Nabilla, Zahra Tazkia Noor; Efianingrum, ariefa (Dimensia: Jurnal Kajian Sosiologi, 2026)
The rise of social media has encouraged Generation Z to use pseudonymous accounts as a means of self-expression in the digital space. The use of these alternative identities aims to protect privacy while providing a sense of security when interacting on social media, particularly X (Twitter). This study employs a qualitative approach using the case study method. Data collection techniques were conducted through observation of pseudonymous account activities, in-depth interviews with informants, documentation, and a literature review of journals and previous studies. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that pseudonymous accounts provide a more comfortable space for Generation Z to express opinions, personal experiences, and social concerns without fear of social judgment.